Analysis of Brand Image as a Mediator between Service Quality and Perceived Price on Tourists' Decision to Stay at Ashley Hotel Wahid Hasyim Jakarta - Joko Haryanto; Bonifasius MH Nainggolan (Dinasti Publisher, 2024)
This research aims to analyze Brand Image as a Mediator between Service Quality and Perceived Price on Tourists' Decision to Stay at Ashley Hotel Wahid Hasyim Jakarta. The population in this study consists of guests who have visited Ashley Hotel Wahid Hasyim at least once, with a sample obtained through purposive sampling of 160 respondents. Data analysis used the Outer model and Inner model (SEM-PLS). The results of the study indicate that overall, Service Quality and Perceived Price have a positive and significant effect on Tourists' Decision to Stay through Brand Image. Brand Image plays a mediating role as an intervening variable between Service Quality and Perceived Price. The implications of this study show that the management of Ashley Hotel Wahid Hasyim can increase Tourists' Decision to Stay by focusing on Service Quality, Perceived Price, and Brand Image.